"Drop metastasis": a rare diagnosis. A case report and review of literature - Ana Simas; Carolina Sales; Maria Fragoso (Sociedade Galega de Medicina Interna, 2017)
"Drop metastasis", also known as intramedullary spinal cord metastasis (ISCM), is a rare complication of cancer, affecting0.1%-0.4% of all cancer patients.It is the rarest type of central nervous system (CNS) involvementby systemic malignant tumours, and it accounts for2%-8.5% of CNS metastasis and 0.9%-5% of all spinalcord metastasis. Before MRI being available, most cases of"Drop metastasis" were diagnosed only upon autopsy. Allthough this rare complication is most commonly secondary to small-cell lung cancer, it can also be seen in non-small-cell lung cancer, breast cancer, kidney cancer, melanoma,and lymphoma.3 The clinical diagnosis of ISCM shouldbe raised in the presence of rapidly progressive neurologic deficit.